Computer-assisted instruction in teaching early childhood literature - Peng, C.F.; Wah, T.Y.; Ishak, Z. (2009)
This paper focused on how computer-assisted instruction may help in teaching early childhood literature. Other than that, it also discusses on the problems of developing and publishing early childhood literature in Malaysia and the solution for the problems. A survey was carried out to find out whether computer aided instruction is one of the best methods to help teaching early childhood effectively. A selected Malay folk tale, its exercises and game will be discussed throughout the paper.